Role of Daptomycin in Cutaneous Wound Healing: A Narrative Review - Giulio Rizzetto; Elisa Molinelli; Giulia Radi; Federico Diotallevi; Oscar Cirioni; Lucia Brescini; Andrea Giacometti; Annamaria Offidani; Oriana Simonetti (MDPI AG, 2022)
Daptomycin is active against Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA) and the on-label indications for its use include complicated skin and skin structure infections (cSSSI). We performed a narrative review of the literature with the aim to evaluate the role of daptomycin in the skin wound healing process, proposing our point of view on the possible association with other molecules that could improve the skin healing process. Daptomycin may improve wound healing in MRSA-infected burns, surgical wounds, and diabetic feet, but further studies in humans with histological examination are needed. In the future, the combination of daptomycin with other molecules with synergistic action, such as vitamin E and derivates, IB-367, RNA III-inhibiting peptide (RIP), and palladium nanoflowers, may help to improve wound healing and overcome forms of antibiotic resistance.